Electrical characterization of commercial GaN LEDs subjected to electron radiation with different conveyor speed per pass - Hedzir, Anati Syahirah; Hasbullah, Nurul Fadzlin; Abdullah, Yusof; Muridan, Norasmahan (IEEE, 2016)
Commercially fabricated nitride-based light emitting diodes (LEDs) is of interest due to its attractive material properties of high temperature tolerance and breakdown strength, making it suitable to be used in extreme environment. Hence, our focus is on the electrical characterization of commercial Gallium Nitride (GaN) subjected to 1000kGy and 1500kGy dose of electron radiation with the conveyor speed were adjusted to 100kGy and 50kGy per pass. Capacitance-voltage (C-V) and current-voltage (I-V) characteristics of commercial GaN LEDs before and after radiation have been investigated. I-V measurement shows no presence of current and measurement of C-V shows no presence of capacitance after irradiated with both dose level at the conveyor speed of 100kGy per pass, indicating an open circuit problem. However, LEDs that were irradiated with the same amount of dose with a conveyor speed of 50kGy per pass shows an increase in reverse leakage current